EFFECT OF DIFFERENT SKIP FEEDING PROGRAMS ON BROILER CHICKS’ PERFORMANCE - & et al., Shawkat (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to find out how the performance of feed at different age periods affect the productive of birds . A total of 240-day-old broiler chicks have been used (Ross 308), were applied. The chick’s groups were assigned to four treatments with every replicates four times and were distributed randomly into 16 groups of 15 chicks of average body weight in each pen. The research was conducted out on chicks two weeks old. T0 (control): (Feed is provided continuously and permanently for birds), T1: Skip every 1 day: (Provide the feed for one day and cut it the next day and so on until the age of 42 days), T2: Skip every 2 days: (Providing the feed for two consecutive days, cutting it the next day, and so on until the age of 42 days), and T3: Skip every 3 days: (Feed is available for three days in front of the chicks, chicks were remained without feeding the next day, and so on until the end of the study so on until the age of 42 days). No significant variations (P ≤ 0,05) were noticed between the various treatments, during the overall period (15-42) days of age in all characteristics of productive performance, while significant differences were found between the factors in the Production Index and Economic Figure. The differences between treatments are limited to the age periods (15-21), (22-28), and (29-42) days in most characteristics of productive performance.